Sekularisasi Ilmu Pengetahuan Modern dan Tantangannya bagi Pendidikan Islam Kontemporer - Endah Maryani; Sumiran (Lembaga Yasin AlSys, 2026)
The secularization of modern science has shaped a scientific paradigm that separates the empirical dimension from transcendental values, thereby presenting challenges for contemporary Islamic education in maintaining the integration of knowledge, faith, and morality amid developments in science, technology, and globalization. This study aimed to analyse the characteristics of the secularization of modern science, identify its impacts on contemporary Islamic education, and formulate strategies for strengthening an Islamic education paradigm oriented towards the integration of knowledge and Islamic values. This study employed a qualitative approach using the library research method. Data were obtained from books, reputable scientific articles, academic documents, and works by scholars of Islamic education and the philosophy of science. The data were analysed using content analysis through the stages of reduction, categorization, interpretation, and conceptual synthesis. The results showed that the secularization of modern science causes epistemological fragmentation, the marginalization of the spiritual dimension in education, the dominance of the positivist paradigm, and the weakening of ethical orientation in the development of science. These conditions affect educational objectives, curriculum structure, learning processes, and students’ character formation in Islamic educational institutions. Contemporary Islamic education has the potential to develop an integrative scientific paradigm through the reconstruction of Islamic epistemology, the strengthening of the Islamic worldview, the integration of revelation and reason, the development of a value-based curriculum, and the revitalization of character education grounded in the Qur’an and Sunnah. This study confirms that strengthening the integrative paradigm is an important foundation for developing Islamic education that is adaptive to advances in modern science without neglecting Islamic identity. These findings provide a conceptual contribution to the development of Islamic education and practical implications for the formulation of educational policies, curriculum design, and learning models that integrate scientific, spiritual, moral, and social dimensions in responding to the dynamics of global civilization.